Low back pain in weightlifters: personalised exercise protocols for elite athletes - Oliva, F.; Agnes, M. N.; Castellano Vitaterna, M.; Maffulli, N. (Muscles, Ligaments and Tendons Journal, 2023)
Background. Most of us has experienced low back pain (LBP) at least one time during his life, but there is no knowledge on weightlifting athletes. Indeed, LBP is one of the most complained injuries, usually caused by disc herniation. The athlete needs to know the correct training technique to reduce stress on joints and to avoid severe injuries. But once the injury has happened, the role of rehabilitation is crucial, because the athlete needs to return to the sport as soon as possible in an optimal condition. Objective. To analyze if the personalized protocol and the specific therapeutic exercises adopted are effective in amateur weightlifters. Patients and methods. LBP has been diagnosed on seven amateur weightlifters out of fifty athletes. We proposed a personalized rehabilitation treatment based on the symptoms of the patients, adapting it to their needs, following them until their return to the sport practice. Results. All patients returned to the sport practice, most of them at the same level as before the injury. One of them returned to the sport practice gradually, but not yet at the same level, and the last one is getting better results compared to the ones before the injury. Conclusions. In our experience, personalizing the rehabilitation on the symptoms of the patient is the key point of the rehabilitation program, as long as choosing the right therapeutic exercises for each patient. Pain and load management is the starting point; the specific exercise selection should be decided upon the level of discomfort the patient can work with.